2019
DOI: 10.1101/619080
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EZHIP constrains Polycomb Repressive Complex 2 activity in germ cells

Abstract: The Polycomb machinery is required for the proper orchestration of gene expression by virtue of its critical role in maintaining transcriptional silencing. It is composed of several chromatin modifying complexes, including Polycomb Repressive Complex 2 (PRC2), which deposits H3K27me2/3. Here, we report the identification of a new cofactor of PRC2, EZHIP (EZH1/2 Inhibitory Protein), expressed predominantly in the gonads. EZHIP limits the enzymatic activity of PRC2 and lessens the interaction between the core co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…Our work highlighted the robust specificity of EZHIP staining in all PF ependymomas, group PFA and in all DMG, H3-wildtype with EZHIP overexpression, ruling out the main differential diagnoses encountered in children in the brainstem and in the posterior fossa (Table 1). All germinomas except two exhibited a strong positivity for EZHIP concomitant with a loss of H3K27me3 as published previously [2,7]. Concerning HGG, MYCN-amplified none of our 9 cases (confirmed by DNA-methylation profiling and previously reported [5,6]), were immunopositive, contrarily to a previous study which reported an expression of EZHIP in 13% of cases [1].…”
supporting
confidence: 88%
“…Our work highlighted the robust specificity of EZHIP staining in all PF ependymomas, group PFA and in all DMG, H3-wildtype with EZHIP overexpression, ruling out the main differential diagnoses encountered in children in the brainstem and in the posterior fossa (Table 1). All germinomas except two exhibited a strong positivity for EZHIP concomitant with a loss of H3K27me3 as published previously [2,7]. Concerning HGG, MYCN-amplified none of our 9 cases (confirmed by DNA-methylation profiling and previously reported [5,6]), were immunopositive, contrarily to a previous study which reported an expression of EZHIP in 13% of cases [1].…”
supporting
confidence: 88%
“…Interestingly, oncohistone H3 lysine 27 to methionine (H3K27M) mutation—found in diffuse intrinsic pontine gliomas (DIPGs)—dominantly inhibits PRC2 activity and reduces global H3K27me3 yet results in DNA hypomethylation (Bender et al , 2013; Lewis et al , 2013). Furthermore, EZHIP/CXORF67 , a germline‐specific gene, encodes a protein that binds to and blocks PRC2 spreading from H3K27me3‐occupied CpG islands through an H3K27M‐like mechanism (Jain et al , 2019; Ragazzini et al , 2019). EZHIP is silenced through promoter methylation in adult tissues, and its de‐repression upon DNA hypomethylation results in PRC2 inhibition (Bayliss et al , 2016; Piunti et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, asymmetric bivalent nucleosomes displayed preference for PRC2 complexes containing EPOP and EZHIP (Figures 3A and S3A). EPOP and EZHIP have been shown to reduce H3K27me3 levels by competing with binding of PRC2 auxiliary subunits such as JARID2 that confer more potent repressive activity to PRC2 (Beringer et al, 2016; Liefke et al, 2016; Ragazzini et al, 2019) and, in the case of EZHIP, also by directly inhibiting PRC2 activity (Hübner et al, 2019; Jain et al, 2019). The bivalency-specific recruitment of EPOP and EZHIP may therefore further contribute to poising by curbing PRC2 activity.…”
Section: Discussionmentioning
confidence: 99%